The dynamics of industrial concentration in Australian manufacturing - Bhattacharya, M.; Bloch, Harry (Elsevier, 2000)
A dynamic model of concentration is developed, with incomplete and industry-specificadjustment to deviations of concentration from its steady state. Cross-sectional analysis iscarried out against a sample of 102 Australian manufacturing industries at the Australian Standard Industrial Classification (ASIC) four-digit level over the period 1977/78-1984/85. The estimated adjustment is faster than found in studies of the more mature industrial economies and this adjustment is found to significantly increase with reductions in tariff protection. There is also empirical support for John Sutton's argument that the relationship between concentration and market size depends on whether set-up costs are exogenous.